ETIKA DALAM PENERAPAN OUTSOURCING INFORMATION TECHNOLOGY DI PERBANKAN - Rahmadya Trias Handayanto (Universitas Bina Sarana Informatika, 2010)
Security and privacy of bank customer is the most important thing when we talk about information technology ethic in bank literature. Security and privacy of bank customer is related to security and privacy of officer such us teller, customer service, sales manager and so on. The information can be found in email, database transaction and other logs information. Trend of using outsourcing in bank makes top level management mast be count its strong and weakness . In outsourcing, the security and privacy of bank customer and officer held by third party institution. This paper is talk about Information Technology (IT) Ethics when bank institution outsource its vital division to third party. Case study of this paper is outsourcing IT at Bank Danamon, Tbk.Key Words: IT Ethics, Outsourcing, Banking.